Penerapan Karakter Mandiri dan Kerja Keras Siswa SD Kota Martapura melalui Penerapan Pendekatan Saintifik K13 - Rusdiyana Rusdiyana (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2019)
Character education in schools must involve curriculum content, the 2013 curriculum emphasizes the scientific approach in the learning process and Some Elementary School implementing Scientific Approach in Martapura. The research aims are to get information about: 1) the scientific approach implementation of the curriculum 2013, 2) the independent character development, and 3) the hard work character development at Elementary School in Martapura. This research is using quantitative approach with survey method that conducted at SDN Jawa 1, SDN Jawa 2, SDN Indrasari 1 and SDN Indrasari 2 in Martapura in South Kalimantan. The sample is 24 teachers at those Elementary Schools. The steps are to formulate: 1) questioner of the scientific approach and independent and hard work character, 2) observation form of the scientific approach implementation and independent and hard work character, and 3) conducted the research at the Elementary Schools implemented scientific approach in Martapura. The data collecting technique is using questioner and visiting class observation. The analysis technique is descriptive. The study result was found that the score avarage of scientific approach score is 82.90 with good category, independent character is 84.35 with good category and work hard character is 78.26 with good category.